1999
DOI: 10.1177/109467059914007
|View full text |Cite
|
Sign up to set email alerts
|

The Antecedents of Customer Loyalty

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Likewise, the relationship marketing concurs customers reciprocate to the marketing activities of businesses that benefit customers (Grönroos, 1994), corroborating the Keller's (2001) view of brand engagement as a 'highly sync' relationship between customers and brands. Additionally, the relationship marketing theory explains that response of customers towards brands originates from the perceived value they derive from brands (Blackwell et al,1999). On the same lines, the benefits customers draw from the brand become the core relational factors that determine the long-term relationship between customers and brands, eventually leading to brand engagement behavior (Bowden, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the relationship marketing concurs customers reciprocate to the marketing activities of businesses that benefit customers (Grönroos, 1994), corroborating the Keller's (2001) view of brand engagement as a 'highly sync' relationship between customers and brands. Additionally, the relationship marketing theory explains that response of customers towards brands originates from the perceived value they derive from brands (Blackwell et al,1999). On the same lines, the benefits customers draw from the brand become the core relational factors that determine the long-term relationship between customers and brands, eventually leading to brand engagement behavior (Bowden, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…found that high perceived value of customers will bring high satisfaction with the products and the customers are likely to choose the enterprise in the future and has a higher loyalty to the enterprise [27]. Based on customer value-customer loyalty model, Blackwell et al (1999) proposed that profits perception, perceived loss of profit, situational and personal preferences affect the perceived value, and perceived value and context have a positive impact on customer loyalty (Blackwell et al, 1999) [28]. This paper presents the hypothesis H4: customer perceived value has a positive impact on customer loyalty.…”
Section: The Relationship Between the Customer Perceived Value And Thmentioning
confidence: 99%
“…Maslow(1943) divided people's demand into five levels: physiological demands, security demands, emotional demands, respect demands and self realization demands; Blackwell(1999) [16] has an opinion that perceived benefits include material factors, service factors, psychological factors. These factors all can be summed up as material demand and spiritual demand.…”
Section: The Incentive Strategies In Online Trading Platform Communitymentioning
confidence: 99%